Evaluation of a Red Cell Leukofilter Performance and Effect of Buffy Coat Removal on Filtration Efficiency and Post Filtration Storage - Sonker, Atul (Indian J Hematol Blood Transfus, 2013)
Prestorage leukoreduction of red cells is effective in reducing the incidence of HLA alloimmunization and improving the quality of stored packed red blood cells (PRBC). This study was conducted to evaluate the effectiveness of Imugard III-RC 4P in removing the leukocyte from packed red cells and the storage effects thereafter. The effects of buffy coat removal on the efficiency of leukofiltration, storage parameters of leukofiltered packed red blood cells and feasibility of prestorage leukofiltration were also assessed. Sixteen units each of buffy coat-depleted (LP) and nondepleted (NLP) PRBC were taken. Every unit was divided into two equal halves, one leukofiltered and other, non-leukofiltered. Cell counts, volume, hematocrit and hemoglobin were measured before and after filtration. Levels of K(+), lactate dehydrogenase (LDH) and hemolysis were assessed in all the units weekly, post leukofiltration. Post leukofiltration, red cell and volume loss was within the specified limit in all the units. Residual leukocytes were significantly lesser in LP- PRBC compared to NLPPRBC. K(+), LDH and hemolysis were significantly elevated in NLP- PRBC. Leukofiltered PRBC showed lesser elevation of K(+), LDH and hemolysis towards the end of the storage period as compared to their unfiltered counterparts. Leukofilter is capable of performing ~4 log reduction. Buffy coat removal prior to filtration improves the efficiency of leukofilter and aids in improving the storage of red cells in terms of hemolysis.